ANALISIS PRAKTIK AKUNTANSI SYARIAH DALAM MANAJEMEN MODAL KERJA UNTUK PENINGKATAN LABA USAHA: STUDI PADA USAHA OCTA LAUNDRY - Randina, Nina; Abdul Mutalib, Ahmad; Masyhuri, Masyhuri (Jurnal Akuntansi AKTIVA, 2025)
This study aims to analyze the practice of sharia accounting in working capital management and its contribution to increasing business profits at Octa Laundry. This study uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation, then analyzed using thematic analysis and triangulation techniques. The results of the study indicate that Octa Laundry has implemented sharia principles such as honesty, transparency, and fairness in working capital management. Although its implementation has not been explicitly documented, these values are reflected in the way the business is managed. This practice also supports business efficiency and contributes to increasing business profits. This study shows that the integration of sharia values in working capital management can be an effective strategy for micro businesses in improving financial performance sustainably